1979
DOI: 10.1159/000176247
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nutrition in the Development of Osteomalacia in the Elderly

Abstract: A dietary survey has been carried out of elderly people with osteomalacia. The commonest type of osteomalacia was that associated with partial gastrectomy. Although a dietary deficiency of vitamin D has been suggested as a cause of the osteomalacia the intake of this substance was not significantly different from that in controls to explain the development of the disease. It was found, however, that patients with osteomalacia went outside much less than controls and given the contribution of sunlight to meetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1979
1979
1995
1995

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In addition, Pun et al (1990) reported significantly lower serum 25-hydroxyvitamin D concentrations in hip fracture patients in Hong Kong, nearly 50% of whom had subnormal levels. Although it is likely that both reduced dietary intake and low sunlight exposure contribute to vitamin D deficiency in the elderly, most evidence suggests that the latter is more important (Aaron et al, 1974a;Hodkinson et al, 1979;Lawson et al, 1979;Lester et al, 1977;Pittet et al, 1979). Other factors may also contribute to vitamin D deficiency in the elderly; these include reduced intestinal absorption of vitamin D ( Barragry et al, 1978), impaired cutaneous synthesis of vitamin D3 (Holick, 1990) and reduced renal synthesis of the active metabolite, 1,25-dihydroxyvitamin D (Slovik et al, 1981).…”
Section: Vitamin D Status In the Elderlymentioning
confidence: 99%
“…In addition, Pun et al (1990) reported significantly lower serum 25-hydroxyvitamin D concentrations in hip fracture patients in Hong Kong, nearly 50% of whom had subnormal levels. Although it is likely that both reduced dietary intake and low sunlight exposure contribute to vitamin D deficiency in the elderly, most evidence suggests that the latter is more important (Aaron et al, 1974a;Hodkinson et al, 1979;Lawson et al, 1979;Lester et al, 1977;Pittet et al, 1979). Other factors may also contribute to vitamin D deficiency in the elderly; these include reduced intestinal absorption of vitamin D ( Barragry et al, 1978), impaired cutaneous synthesis of vitamin D3 (Holick, 1990) and reduced renal synthesis of the active metabolite, 1,25-dihydroxyvitamin D (Slovik et al, 1981).…”
Section: Vitamin D Status In the Elderlymentioning
confidence: 99%
“…The incidence depends on the type of operation performed [3], on the methods used to detect the altered bone metabolism [2], and on the selection of the patient material.The pathogenesis is still debated. Factors suggested include malabsorption of vitamin D and calcium, altered enterohepatic circulation of vitamin D, insufficient diet (especially fat and calcium containing food products), and reduced exposure to sunlight [4][5][6].The purpose of this study was to establish the degree of altered bone metabolism in a well defined population of gastrectomized…”
mentioning
confidence: 99%
“…The pathogenesis is still debated. Factors suggested include malabsorption of vitamin D and calcium, altered enterohepatic circulation of vitamin D, insufficient diet (especially fat and calcium containing food products), and reduced exposure to sunlight [4][5][6].…”
mentioning
confidence: 99%
“…To investigate further the effect of cholestasis on 25 hydroxylation in man we have studied the metabolism of intravenously injected 3HD3 in patients with acute cholestasis due to extrahepatic bile duct obstruction as well as in patients with chronic cholestasis (PBC). Malabsorption of vitamin D does occur in PBC (Krawitt et al, 1977) but this is unlikely to be a major cause of the low plasma 250HD in this condition, as ultra-violet light is the more important source of 840 vitamin D in man (Preece et al, 1975;Pittet et al, 1979;Poskitt et al, 1979). We have therefore also investigated the response of jaundiced patients with PBC to ultra-violet irradiation.…”
mentioning
confidence: 99%